Analysis of Zoning Systems and Patterns of Passenger and Vehicle Traffic at the Bungus Bay Crossing Port - Yeti Komalasari; Monica Amanda; Denis Afandi (IWJ : Inland Waterways Journal, 2021)
Bungus Bay Ferry Terminal is the only access for vehicles and passengers between Padang City and the Mentawai Islands Regency. Mentawai Islands Regency is a separate district from West Sumatra Province, which is located in the westernmost island of Sumatra and is surrounded by the waters of the Indian Ocean. There are 2 (two) Ro - Ro ships belonging to PT. ASDP Indonesia Ferry (Persero) Padang branch serving the Padang - Mentawai Islands route. The existence of this Ferry Port is very important in an effort to support economic development and progress in the Mentawai Islands. However, at this time the crossing port zoning system has not been implemented which causes the traffic flow pattern of passengers and vehicles at this port to not run well. It is necessary to implement a Ferry Port zoning system with zoning restrictions based on PM 29/2016 concerning the Sterilization of Ferry Ports and to apply regulations on traffic flow patterns for passengers and vehicles based on SK.242 / HK.104 / DRJD / 2010 concerning Technical Guidelines for Cross Traffic Management.